14C data of three North Atlantic sediment cores during the Holocene - Lukas Gerber; Jörg Lippold; Cristiano Mazur Chiessi; Sönke Szidat (PANGAEA, 2025)
To examine the variability of the Atlantic Meridional Overturning Circulation (AMOC) during the Holocene in the North Atlantic, we developed new age models for three sediment cores (ODP 172-1063, ODP 172-1059, and GeoB18529-2). These models were based on radiocarbon (14C) ages of mixed planktonic foraminifera species, measured by accelerator mass spectrometry at the University of Bern, ETH Zurich, and Beta Analytic Inc. The new Holocene age models were calibrated using rbacon (v3.3.1) with Marine20, with a weighted mean of ten location-specific reservoir age offsets (ΔR), to account for the local marine reservoir effect.